Differentiation of cardiac thrombus from cardiac tumor combining cardiac MRI and 18F-FDG-PET/CT Imaging. (1st June 2016) - Rinuncini, Massimo; Zuin, Marco; Scaranello, Fiorenzo; Fejzo, Majlinda; Rampin, Lucia; Rubello, Domenico; Faggian, Giuseppe; Roncon, Loris
Abstract: Radiological differentiation of an unknown cardiac masse is often a challenging issue. 18F-FDG-PET/CT imaging was performed to evaluate a left ventricle mass visualized on transthoracic echocardiogram (TTE) and cardiac magnetic resonance (CMR) in a patient with an history of ischemic heart disease. The metabolically inert area on the PET/CT, corresponding to the relatively homogenous hypodensity in the LV, was thought to represent an old organized LV thrombus. Histopathological examination confirmed the imaging diagnosis